Relationship between ground reaction force in horizontal plane and mechanical energy flow in torso during baseball tee batting - Horiuchi, G.; Nakashima, H. (Sports Biomechanics, 2023)
The purpose of this study was to clarify the relationship between the ground reaction force (GRF) in the horizontal plane and the mechanical energy flow in the torso during baseball tee batting. The batting motion and GRF acting on each foot of 30 collegiate baseball players were recorded using a motion capture system and two force plates. To measure the mechanical energy inflow into the torso from both hip joints, the mechanical power of the torso by the force and torque of both hip joints was calculated. The horizontal GRF variables of the stride foot were significantly correlated with mechanical energy inflow into the lower torso from the hip joint of the stride foot side. Conversely, the horizontal GRF variables of the pivot foot were not significantly correlated with mechanical energy inflow into the lower torso from the hip joint of the pivot foot side. Thus, these results suggest that exploring the posture easily to receive the horizontal GRF by the stride foot (i.e., optimisation of magnitude and/or angle of GRF acting on the stride foot) increases the mechanical energy inflow into the lower torso from the hip joint of the stride foot side during baseball batting.